A Family Affair: Addressing the Challenges of Factor H and the Related Proteins - Poppelaars, Felix; Goicoechea de Jorge, Elena; Jongerius, Ilse; Baeumner, Antje J.; Steiner, Mark-Steven; Józsi, Mihály; Toonen, Erik J. M.; Pauly, Diana; , the SciFiMed consortium (Frontiers in Immunology, 2021)
Inflammation is a common denominator of diseases. The complement system, an intrinsic part of the innate immune system, is a key driver of inflammation in numerous disorders. Recently, a family of proteins has been suggested to be of vital importance in conditions characterized by complement dysregulation: the human Factor H (FH) family. This group of proteins consists of FH, Factor H-like protein 1 and five Factor H-related proteins. The FH family has been linked to infectious, vascular, eye, kidney and autoimmune diseases. In contrast to FH, the functions of the other highly homologous proteins are largely unknown and, hence, their role in the different disease-specific pathogenic mechanisms remains elusive. In this perspective review, we address the major challenges ahead in this emerging area, including 1) the controversies about the functional roles of the FH protein family, 2) the discrepancies in quantification of the FH protein family, 3) the unmet needs for validated tools and 4) limitations of animal models. Next, we also discuss the opportunities that exist for the immunology community. A strong multidisciplinary approach is required to solve these obstacles and is only possible through interdisciplinary collaboration between biologists, chemists, geneticists and physicians. We position this review in light of our own perspective, as principal investigators of the SciFiMed Consortium, a consortium aiming to create a comprehensive analytical system for the quantitative and functional assessment of the entire FH protein family.